Pengaruh Mencari Variasi, Ketidakpuasan Konsumen, Harga dan eWOM Terhadap Perpindahan Merek - A. Rossy Indriani; Yusepaldo Pasharibu (JURNAL EKOBIS DEWANTARA, 2020)
Product competition among producers will have an impact on the vulnerability of brand transfer. A brand transfer is a buying pattern that is associated with a change from one brand to another. Some factors that are suspected to influence brand transfer are due to the need to seek variations, consumer dissatisfaction, price, and e-WOM. The purpose of this study is to determine whether there is an influence of the need to seek variations, consumer dissatisfaction, price and eWOM on brand transfer decisions with studies conducted on Samsung Galaxy brand users who switch to the iPhone brand. This quantitative study uses a purposive sampling technique with a total sample of 100 respondents. The instrument used for data collection was using a Likert scale questionnaire. Then the data is processed by using multiple regression analysis. Finally, the results showed that the need to seek variations, consumer dissatisfaction, price and eWOM had a significant influence on brand switching decisions.